Design and engineering of organic molecules for customizable terahertz tags - Ray, Shaumik; Dash, Jyotirmayee; Nallappan, Kathirvel; Kaware, Vaibhav; Basutkar, Nitin; Ambade, Ashootosh; Joshi, Kavita; Pesala, Bala (Terahertz, RF, Millimeter, and Submillimeter-Wave Technology and Applications VII, 2014)
Terahertz (THz) frequency band lies between the microwave and infrared region of the electromagnetic spectrum. Molecules having strong resonances in this frequency range are ideal for realizing "Terahertz tags" which can be easily incorporated into various materials. THz spectroscopy of molecules, especially at frequencies below 10 THz, provides valuable information on the low frequency vibrational modes, viz. intermolecular vibrational modes, hydrogen bond stretching, torsional vibrations in several chemical and biological compounds. So far there have been very few attempts to engineer molecules which can demonstrate customizable resonances in the THz frequency region. In this paper, Diamidopyridine (DAP) based molecules are used as a model system to demonstrate engineering of THz resonances (< 10 THz) by fine-tuning the molecular mass and bond strengths. Density Functional Theory (DFT) simulations have been carried out to explain the origin of THz resonances and factors contributing to the shift in resonances due to the addition of various functional groups. The design approach presented here can be easily extended to engineer various organic molecules suitable for THz tags application.